MODERN CHINESE LITERATURE WITH THE ABSENCE OF THE RUSSIAN SCHOOL OF FORMALISM - Hue, Dao Thu (VNU Journal of Foreign Studies, 2018)
Modern Chinese literature was formed and developed in the early 20 th century at the same time as the formation of the Russian School of Formalism. Using the methods of synthesis and analysis, the article points out the importance of literary theory in the Russian School for the development of literature. The research results show that when the Russian School of Formalism was not accepted in China, Chinese modern literature experienced a long period of development that focused on spreading content but ignored art and was easily manipulated by politics. Consequently, its content and art as well as authors and creative forces were negatively affected. By contrast, when the Russian Formalism School was accepted, modern Chinese literature had great achievements in terms of content and art forms. Thereby, the article proves that freedom to reception of artistic ideas in artistic and literary creation is extremely important.